2018
DOI: 10.1017/s0007114518002040
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of impaired fasting glucose and diabetes among Chinese children and adolescents: a national observational study

Abstract: The prevalence of impaired fasting glucose (IFG) and diabetes mellitus (DM) has reportedly increased significantly among Chinese children and adolescents. We aimed to examine the prevalence of IFG and DM, the disparities in sex and region and related risk factors among Chinese children and adolescents. A total of 16 434 Chinese children aged 6-17 years were selected from a national cross-sectional survey, and fasting glucose was measured for all participants. Overall, mean fasting plasma glucose (FPG) concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
(39 reference statements)
9
15
1
Order By: Relevance
“…In addition, urban children in our study were more likely to be diagnosed with IFG than rural children, which is consistent with the finding of the study in China [29]. Urban children may be associated with more unhealthy behaviors than their rural counterparts, such as higher consumption of fried foods and carbonated soft drinks, and higher prevalence of physical inactivity, which might be associated with the difference in IFG prevalence [29]. We found that the age of children was negatively associated with IFG; however, in our study, we only included participants aged 11-14 years old, so the association might not be significant for an expanded age group.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In addition, urban children in our study were more likely to be diagnosed with IFG than rural children, which is consistent with the finding of the study in China [29]. Urban children may be associated with more unhealthy behaviors than their rural counterparts, such as higher consumption of fried foods and carbonated soft drinks, and higher prevalence of physical inactivity, which might be associated with the difference in IFG prevalence [29]. We found that the age of children was negatively associated with IFG; however, in our study, we only included participants aged 11-14 years old, so the association might not be significant for an expanded age group.…”
supporting
confidence: 92%
“…We also observed a higher prevalence of obese children with a diagnosis of IFG. In addition, urban children in our study were more likely to be diagnosed with IFG than rural children, which is consistent with the finding of the study in China [29]. Urban children may be associated with more unhealthy behaviors than their rural counterparts, such as higher consumption of fried foods and carbonated soft drinks, and higher prevalence of physical inactivity, which might be associated with the difference in IFG prevalence [29].…”
supporting
confidence: 90%
See 1 more Smart Citation
“… 21 In China, the prevalence of diabetes and IFG was 0.13% and 2.26% of children aged 10–17 years based on secondary school exams during 2013–2014. 22 Fu et al 23 reported youth-onset type 2 diabetes increased from 4.1/100,000 (1995–2000) to 10.0/100,000 (2005–2010). The listed studies are difficult to compare because of the study population's different ethnic and age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies were conducted among school-age children and adolescents. 9,[19][20][21] Although some of them contained children of young age as part of the study subjects, their data were not presented or described as a separate age group. 19,20 Pre-school is a unique stage of life cycle, and could have different characteristics in terms of DM, IFG, obesity and susceptible behaviours as compared to other age groups.…”
Section: Discussionmentioning
confidence: 99%